SEKOLAH ISLAM TERPADU PRESPEKTIF MULTIDISIPLINER - Rio Kurniawan (Institut Islam Mamba'ul 'Ulum Surakarta, 2020)
The Integrated Islamic School (SIT) is currently one of the educational institutions that receives broad responses from the Indonesian Muslim community. That is evidenced by the increasing number of parents who send their children to various levels of SIT, from kindergarten, elementary school, junior high school to high school. At present there are thousands of Integrated Islamic Schools gathered under the auspices of the Integrated Islamic Schools Network (JSIT) and there are also many private schools developed by social and religious organization foundations in Indonesia called IT Schools and that follows the system. Integrated Islamic Schools are essentially schools that implement the concept of Islamic education based on the Qur'an and Sunnah. This paper tries to answer some questions of the Integrated Islamic School through the perspective of History, Social and Politics and as a dissection knife from the Integrated Islamic School of Multidisciplinary Perspective and the Integrated Islamic School as a Renewal of the Islamic Education System.